Enhancing Moral and Religious Values Through Storytelling in Sari Mekar Kindergarten, West Halmahera: Improving Moral and Religious Values ​​Through Storytelling in Kindergarten - Nurhumairah; Rita Samad; Nurul Jariah; Sarina (Creative Smart Visionary, 2025)
The aim of this study was to improve moral and religious values in early childhood through storytelling activities at Sari Mekar Kindergarten in Lako Akediri Village, Sahu District, West Halmahera Regency. The research method used was Classroom Action Research (CAR) conducted in two cycles. The research subjects were 20 children in class A. Data collection wwerecarried out through observation, documentation, and daily assessments, which were then analyzed using data reduction, data presentation, conclusion drawing, and descriptive qualitative and quantitative verification by calculating the percentage of achievement of moral and religious value indicators. The results of the study showed a significant increase in children's moral and religious values from the pre-action stage to cycle II. In the pre-action stage, 90% of children were in the underdeveloped category and only 5% were in the developed category as expected. After the storytelling activity was implemented, cycle I showed that 85% of children were in the underdeveloped category, 10% were in the beginning to develop category, and 5% had reached the expected developing category. Cycle II showed that 80% of children had reached the expected developing category and were developing very well, while the rest were beginning to develop. These changes were evident in the children's behavior, as they became accustomed to worshipping, understood noble behavior, could distinguish between good and bad behavior, became familiar with religious rituals and holidays, and respected other people's religions. Thus, storytelling activities proved to be effective in instilling moral and religious values in early childhood.